Clinical epidemiology and costs of type 2 diabetic patients with or without prior coronary artery disease or stroke. A longitudinal 5-year claims-data analysis of over 7 million inhabitants. (14th October 2021) - Maggioni, A P; Dondi, L; Andreotti, F; Ronconi, G; Calabria, S; Piccinni, C; Pedrini, A; Esposito, I; Martini, N
Abstract: Aims: Contemporary, real-world data on type 2 diabetes mellitus (T2DM) are limited. We analysed prevalence, comorbidities, outcomes and costs of T2DM patients with and without coronary artery disease (CAD) or stroke in >7 million inhabitants. Methods: T2DM patients were identified in 2015 (accrual period) from the Ricerca e Salute (ReS) database linking administrative records to demographics. From 2013–2015 information, four cohorts were considered: #1 with CAD and/or stroke; #2 without CAD and/or stroke; #3 with chronic CAD but no myocardial infarction or stroke; #4 with chronic CAD undergoing percutaneous coronary interventions (PCI). Hospitalizations, drugs and other outpatient care were assessed from 2015 to 2017. Results: Prevalence of T2DM was 6% (441, 085/7, 365, 954). CAD and/or stroke in the previous 3 years affected 7.5% of T2DM patients (33, 153); this cohort was generally older, of male sex, with more comorbidities, prescriptions, and hospital admissions (50% versus 13.4%) compared to cohort #2. Yearly costs were >3-fold for cohort #1 versus #2, main drivers being hospitalizations in the former and drugs in the latter. Unexpectedly, two-year cardiovascular events were significantly higher in cohort #4 compared to any other (Figure). Guideline-recommended therapies were suboptimal in all cohorts. Conclusions: The present analysis points to three areas of potential improvement in T2DM management: 1) undertreatment of T2DM patients with recommended drugs; 2) three-fold recurrences and costs in T2DM patients with, compared to those without, prior cardiovascular events; 3) highest risk of events in those with chronic CAD and PCI, warranting specific studies aimed at defining more effective preventive strategies. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): This research was partially supported by an unrestricted grant from Astra Zeneca. Astra Zeneca was not involved in data collection, analysis and interpretation, in writing the report, nor in deciding to submit the article for publication.